Subgroup Formation in Diverse Virtual Teams: The Moderating Role of Identity Leadership - op ‘t Roodt, Helen; Krug, Henning; Otto, Kathleen (Frontiers in Psychology, 2021)
As today’s organizations are becoming increasingly globalized and adding the impetus to a more remote form of working due to the present COVID-19 pandemic, new ways of collaboration – like virtual teams – have gained importance. Even though the combination of diverse skills and backgrounds can be beneficial for team outcomes, virtual team members might become aware of existing differences among their colleagues, and self-categorization processes can lead to the formation of subgroups. In the present cross-sectional study, a total of 102 virtual team members participated in an online survey to investigate the factors moderating the relationship between subjectively perceived diversity and subgroup formation as well as between perceived diversity and team performance and satisfaction. Moderation analysis revealed that subjective diversity had a negative influence on performance ratings when subgroups were highly perceived to be present, but not if subgroup formation was rated as low. The relationship between perceived diversity and team satisfaction was not moderated by perceived subgroup formation. Furthermore, identity leadership was found to be positively related to team satisfaction and perceived performance, while subjective diversity was negatively associated with both team outcomes. High levels of identity leadership were shown to weaken the positive relationship between perceived diversity and subgroup formation. This study points to the importance of the team leader's role as a manager of a shared social identity in virtual teams where perceived differences can lead to subgroup splits.